The algebra of wealth : a simple formula for financial security - Galloway, Scott, 1964- (Portfolio/Penguin, 2024)
"A must-have guide to optimizing your life for wealth and success, from bestselling author, NYU professor and co-host of the Pivot podcast Scott Galloway. Today's workers have more opportunities and mobility than any generation before. They also face unprecedented challenges, including inflation, labor and housing shortages, and climate volatility. Even the notion of "retirement" is undergoing a profound rethink, as our lifespans extend and our relationship with work evolves. In The Algebra of Wealth, Galloway lays bare the rules of financial success in today's economy. In characteristic unvarnished, no-BS style, he explains you what you need o know in order to better your chances for economic security no matter what. Bursting with practical, game-changing advice from one of the world's most popular business school professors, The Algebra of Wealth is the practical guidebook you need to win today's wealth game"--